Speech genres, heuristics and heuristics - Zakirova Dilrabo Khaidarova (Central Asian Journal of Literature, Philosophy and Culture, 2022)
Based on the linguistic research of the Russian linguist M.M. Bakhtin, the composition of speech genres, heuristics and heuristics, V.V. Demeter thinks about the main concept of the speech genre.